Characteristics of Plasmablast Repertoire in Chronically HIV-Infected Individuals for Immunoglobulin H and L Chain Profiled by Single-Cell Analysis - Liao, Hongyan; Li, Song; Yu, Yangsheng; Yue, Yinshi; Su, Kaihong; Zheng, Qin; Jiang, Nenggang; Zhang, Zhixin (Frontiers in Immunology, 2020)
Characterization of the diversified immunoglobulin (Ig) repertoire may provide insight into pathways that shape an efficient antibody (Ab) repertoire for immune response against human immunodeficiency virus (HIV) infection. This study aimed to profile characteristics of plasmablast repertoire during chronic HIV infection. Ig variable regions of plasmablasts from both chronically HIV-infected donors (HIVD) previously treated with antiretroviral therapy and healthy donors (HD) were amplified by single-cell PCR to establish the basis for further repertoire analysis. We compared the plasmablast repertoires expressed in multiple chronically HIVD after ART treatment cessation and HD. We also examined the nonproductive repertoire to identify the indication of the immediate products of the rearrangement machinery without an impact of selection during HIV infection. We found multiple differences between the productive repertoires of HIVD and HD subjects, including biased usages of VH3-49, VH1-2, VH3-33, VH3-74 and VH5-51 in VH and D1-7, D1-14, D1-20, and D5-5/18 in D segments in the HIVD group, as well as shorter and preferential glycine usages in CDRH3 regions. Gene selections were also detected in light chains. Notably, differences between productive rearrangements of HIVD and HD outnumbered those between productive and nonproductive rearrangements within HIVD. HIV infection may exert a dominant impact on the development of the plasmablast repertoire. The impact of selection is of limited significance in shaping the plasmablast repertoire. Overall, the data indicate that the environment in which the plasmablasts live can affect the distribution of the VH and VL genes in the repertoire and the amino acid compositions of the expressed antibodies.